Innovation of CRAM flap for reconstruction of high-voltage electrical burn injuries: Case series - Kawilarang Bertha; Putu Riasa I.Nyoman (Scripta Medica)
Electrical burns cause devastating injury with major soft tissue loss and pose a major threat to life. The damage caused by electrical injuries can extend to deeper tissues, causing exposed soft tissues such as tendon and nerve. The rectus abdominis muscle is a donor of musculocutaneous flap due to the well-known blood supply and high vascularity. The rectus abdominis pedicled flap can be either performed transversely or vertically oriented. The drawback of both of these techniques is the insufficient coverage particularly when used for wide or circular defects. Crescent-shaped rectus abdominis musculocutaneous (CRAM) flap is an innovation that is intended to be used for coverage of circumferential defects with extensive soft tissues exposed as can be seen in the defect caused by electric burn injury. In this paper, cases of high-voltage electrical injury at different anatomical regions which were successfully reconstructed with CRAM flap are presented. Overall, CRAM flap was a reliable flap resulting in well-vascularised soft tissue coverage and acceptable functionality.